Doktrin Pembenaran Oleh Iman Menurut Roma 4:1-25 Sebagai Dasar Keselamatan Kekal Dalam Pembinaan Warga Gereja GBI Epicentre of Mercy Cimanggis - Gangsar Sugio Pranoto (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2024)
This article discusses the doctrine of justification by faith according to Romans 4:1-25 as the basis for eternal salvation in the Church Community Development of the GBI Epicentre of Mercy Cimanggis. Reflecting on the many doctrinal teachings that deny the truth, such as the teachings of Hyper Grace by Joseph Prince, Corpus Delicti and Salvation Outside of Christianity, by Erastus Sabdono and Progressive Christian by Brain Siawatra. So the author wants to straighten out this teaching in the Bible Study (PA) series in the congregation. The  research  method  used  by  the  author  is  a  biblical  theology  research  method  which  is categorized as a biblical hermeneutics method which is the same as hermeneutical phenomology, namely researching texts in an effort to find the meaning of these texts both for first readers (what it means) and for future readers now (what it means), by analyzing verses and literature related to the subject of this research. Especially exploring Romans 4:1-25 in a structured manner. The researcher's conclusion is that the apostle Paul used the examples of father Abraham and King David as proof that a person is justified by God because of his faith, not because of his works. The righteousness that God gives is more like a gift, not as a right that someone receives because they have carried out a certain obligation, and circumcision is a sign that someone has been justified, not a condition for someone to be justified by God.